Exploring Municipal Solid Waste Dynamics in Rural Cambodia: Insights from Three Underrepresented Cities - Kohei Hibino; Chochoe Devaporihartakula; Phalla Sam; Rithy Uch; Bophaphal Sean; John Chek; Sophalin Sen; Premakumara Jagath Dickella Gamaralalage; Yasuhiko Hotta (Waste)
(1) The enactment of Sub-Decree No. 113/2015 on Solid Waste Management marked a significant policy shift towards the decentralisation of waste management in Cambodia and some progress has been observed in Phnom Penh and some other large cities and tourist destinations. However, information in rural areas is lacking. Rapid and simple waste assessment methodologies are needed in rural areas where waste data is scarce and different waste management measures are required compared to urban areas. This study aimed to fill the information gap on the status and fate of municipal solid waste management in rural areas by focusing on three underrepresented cities in different geographical areas through empirical studies. (2) Rapid waste assessments, including waste composition analysis, truck scaling, waste recovery surveys, waste flow analysis, and waste hotspot surveys, were conducted. (3) The per capita waste generation averaged 0.44 kg/day, which is lower than the national average, but did not show significant differences between income levels. The waste composition was similar to that of urban areas, with plastics making up more than 20% of the waste. There were major contrasts in the waste collection rates, with one city having a high rate (85.9%) while the other two cities were as low as 22.6% and 24.2%, respectively. This suggests that rural cities in Cambodia are at different stages of transition in establishing their waste management systems after the decentralisation of waste management to municipalities. The main cause of the low waste collection rate was that private waste collectors were finding it difficult to collect service fees. In the absence of waste collection services, a total of 370 waste hotspots were identified outside of the waste collection areas, where littering and open burning of waste were common. (4) Addressing these challenges requires urgent development of sustainable financing mechanisms, enhanced institutional capacities, and implementation of targeted awareness-raising programmes. These measures are essential for providing basic waste collection and disposal services, as well as for curbing littering and open burning of waste in rural cities in Cambodia.